Bioinformatic Analysis of Transcriptomic Data Reveals Novel Key Genes Regulating Osteogenic Differentiation of Human Adipose Stem Cells - Jinluo Cheng; Xinyuan Zhao; Juan Liu; Li Cui; Yanfeng Zhu; Xiaoqing Yuan; Jianbo Gao; Yunfeng Du; Xinmin Yan; Shen Hu (Stem Cells International)
Adipose stem cells (ASCs) are an attractive cell source for treating many human diseases including osteoporosis. However, the molecular mechanisms accounting for ASC osteogenesis are poorly known. In this study, ASCs were first isolated from the fat tissues from the patients with osteoporosis. The global transcriptome profile between osteogenic differentiated ASCs and undifferentiated ASCs was compared using RNA sequencing (RNA-seq). Then, bioinformatic analysis was performed to reveal the central genes and pathways that regulated the osteogenic differentiation of ASCs. One of the interested genes C5AR1 was chosen for further investigation. A total of 1521 upregulated and 3020 downregulated genes were identified between the ASCs with osteogenic induction and controls. Functional gene ontology analysis revealed that these significantly differentially expressed genes (DEGs) were associated with cell cycle, protein binding, and nucleotide binding. Pathway analysis showed that many canonical pathways, such as the MAPK signaling pathway and the PI3K-AKT pathway, might actively be involved in regulating osteogenic differentiation of ASCs. A total of three subnetworks and 20 central nodes were identified by the protein-protein interaction analysis. In addition, the expression level of C5AR1 was significantly increased during osteogenic differentiation of ASCs. The downregulation of C5AR1 dramatically reduced the expression levels of osteogenic differentiation biomarkers and calcium nodule formation capacity. Collectively, we have provided a number of novel genes and pathways that might be indispensable for ASC osteogenic differentiation. Manipulating the levels of this candidate gene might contribute to the osteoporosis therapy.